Lactobacillus paraplantarum 11-1 Isolated from Rice Bran Pickles Activated Innate Immunity and Improved Survival in a Silkworm Bacterial Infection Model - Nishida, Satoshi; Ishii, Masaki; Nishiyama, Yayoi; Abe, Shigeru; Ono, Yasuo; Sekimizu, Kazuhisa (Frontiers in Microbiology, 2017)
Lactic acid bacteria (LAB) have high immune system-stimulating activity and are considered beneficial for human health as probiotics in the gut. The innate immune system is highly conserved between mammals and insects. Microbe-associated molecular patterns (e.g., peptidoglycan and β-glucan) induce cytokine maturation, which, in silkworm larvae, leads to muscle contraction. The purpose of this study is to find a novel probiotic by using silkworm muscle contraction assay. In the present study, we isolated LAB derived from rice bran pickles. We selected highly active LAB to activate the innate immune system of the silkworm, which was assayed based on silkworm muscle contraction. Of various LAB, L. paraplantarum 11-1 strongly stimulated innate immunity in the silkworm, leading to stronger silkworm contraction than a dairy-based LAB. Silkworms fed a diet containing L. paraplantarum 11-1 exhibited tolerance against the pathogenicity of Pseudomonas aeruginosa. These findings suggest that L. paraplantarum 11-1 could be a useful probiotic for activating innate immunity.